Social media influence in telemedicine for online patient doctor consultation - Al-Battat, Khalil Rafiq; Iyer, Shankar Subramanian (Edelweiss Applied Science and Technology, 2025)
Integrating social media into telemedicine has reshaped the landscape of patient-doctor interactions, enhancing accessibility, engagement, and the dissemination of medical information. This research aims to explore the influence of social media in facilitating online patient-doctor consultations, particularly focusing on how social media tools and platforms contribute to patient awareness, trust-building, and decision-making processes. The research is based on the conceptual model developed using the integrated Technology Acceptance Model (TAM) and Social Cognitive Theory (SCT). Through a qualitative approach involving 15 in-depth interviews with healthcare professionals and patients actively engaged in telemedicine, this study seeks to uncover how social media impacts the quality and outcomes of virtual medical consultations. The findings are expected to provide insights into the benefits, challenges, and potential strategies for optimizing social media's role in telemedicine.